A novel distance-assisted localization algorithm in wireless sensor networks - Xuemai Gu; Yanjun Jiang; Shuo Shi (2010 International Conference On Computer Design and Applications, 2010)
In wireless sensor networks, calculation and management of node position is a subject which has a profound theoretical basis and wide range of application. Due to the randomness of sensor network nodes and the dynamic variability of network topology, lots of algorithms can not meet the requirements of positioning accuracy. For this reason, a DV-DScale localization algorithm is proposed in this paper based on distance-assisted and hop quantization. In the algorithm, cumulative distance value is no longer directly used for maximum likelihood estimation to localization, but as scale to amend the straight-line distance between nodes and estimate the position information of nodes. Because of the low resolution of hops, the traditional localization algorithm which is based on hop can only adapt to the isotropic dense networks. The simulation results show that the proposed algorithm effectively ameliorate the positioning accuracy. Even in the case of random distribution of nodes, the algorithm can also get a higher positioning accuracy.